Study on Water Environmental Characteristics Based on Comprehensive Pollution Assessment Method with Entropy Weight Optimization - HUANG Wen (Renmin Zhujiang)
Evaluating the trends in the water environmental changes of Sand Lake holds positive significance for the improvement and protection of the lake's water environment. To assess the characteristics of the water environment in the Sand Lake in Ningxia, various methods are employed, including the single-factor method, the multi-factor synthesis method, and the comprehensive pollution index method that utilizes entropy weight optimization. These methods are applied based on multi-point monitoring data collected at different times and across various years. The results show that the main pollution factors of Sand Lake water are total phosphorus (TP) and total nitrogen (TN), followed by chemical oxygen demand by permanganate (CODMn) and biochemical oxygen demand (BOD5). At the same time, the comprehensive pollution assessment method, enhanced by entropy weight optimization, indicates that the water quality of Sand Lake in August is classified as category V, exceeding the standard, and the pollution level in summer and autumn in August is significantly higher than that in winter and spring, especially the monitoring point L05, indicating that the lake environment is significantly affected by wildlife such as birds and fish. Finally, the water environmental pollution index values of Sand Lake in 2020 are lower than those monitored in the same period of 2019, suggesting that the water quality of the lake shows an upward trend of change. By using the improved entropy weight optimization method on top of single-factor and multi-factor evaluations, a deeper understanding of the Sand Lake water environment is achieved, providing a reference for future water purification and countermeasures in Sand Lake.